222k views
4 votes
If g(x) =4x+2 and f(x) =3x-10

find g(f(3))

1 Answer

2 votes

Answer:


g(f(3))=-2

Explanation:

So we have the two functions:


g(x)=4x+2\text{ and } f(x)=3x-10

And we want to find g(f(3)).

So, let's find f(3) first:


f(3)=3(3)-10

Multiply:


f(3)=9-10

Subtract:


f(3)=-1

Therefore, we can substitute -1 for f(3):


g(f(3))=g(-1)

Now, find g(-1):


g(-1)=4(-1)+2

Multiply:


g(-1)=-4+2

Add:


g(-1)=-2

And we're done!

So:


g(f(3))=-2

User MamathaMacherla
by
4.9k points